Hubungan Pembelajaran Daring dan Karakter Jujur Siswa Kelas 3 Sekolah Dasar - Alya Setyaningtyas; Nina Nurhasanah; Arifin Maksum (SAP (Susunan Artikel Pendidikan), 2023)
The emergence of the Covid-19 pandemic in Indonesia in 2020 caused the learning system throughout Indonesia to change drastically. This happens at all levels of education, including at the elementary school level. Several previous studies stated that there was an increase in student grades, but the character and effectiveness of learning actually decreased. This research was carried out to determine the relationship between online learning and the honest character of class III students at Setu 02 State Elementary School after the Covid-19 pandemic. This research, which was carried out in 2023, used quantitative methods with product moment correlation analysis techniques using the Microsoft Excel application. This research took samples from class III students at SDN Setu 02 from the student population in Setu sub-district using probability sampling. The correlation coefficient from this research is 0.653 which is on a scale of 0.41 – 0.70, which is sufficient. So, the results of this research are that there is a sufficient correlation between online learning and the honest character of class III students.